The Influence of the Inquiry Learning Model on Student Learning Outcomes in Social Studies Subject Class VI SD Inpres 1 Tanamodindi - Ade Yemifaira; Nashrullah Nashrullah; Yusdin Gagaramusu (FKIP - Universitas Riau, 2026)
Low learning outcomes in elementary-level social studies courses frequently arises from instructional approaches dominated by teachers, which restrict pupils from independently exploring and internalizing subject concepts. This condition demands the implementation of more innovative learning models to encourage student participation and understanding. This research aims to examine the impact of the inquiry-based instructional approach on the academic results of 6th grade pupils in social studies at SD Inpres 1 Tanamodindi. The investigation included 26 participants from class VI B, selected through purposive sampling, with evidence gathered via assessment tests and documentation. Findings indicated that student mean scores rose from 45.19 prior to intervention to 72.11 after intervention. Statistical analysis using the t-test produced a significance level of 0.000, below the threshold of 0.05, leading to rejection of H0 and confirmation of Ha. Consequently, it can be inferred that the inquiry learning approach significantly influences academic performance in grade six social studies.